2017
DOI: 10.5455/jicm.26-20170707
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Anti-Dsdna, Complement Components C3, C4 and Systemeic Lupus Erythematosus Disease Activity Index

Abstract: Anti-dsDNA antibodies were the first autoantibodies described in patients with SLE. Anti-dsDNA antibodies can be found in up to 70% to 80% of patients with SLE at some time during the course of the disease, these antibodies are very rarely found in patients with other autoimmune conditions and in healthy controls. Furthermore, in many cases there is a relationship between disease activity and the titer of anti-dsDNA. In a larger study, Swaak showed that rise in levels of anti-dsDNA antibodies preceded renal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Farkhati et al 22 stated that in SLE patients with positive anti-dsDNA levels, severe disease activity was present and they had higher mortality rate. Another study from Dhason et al 23 revealed that anti-dsDNA antibody level was positive in 83% of all patients with active lupus and 66% of them had high titre of anti-dsDNA levels (>10 IU/ml). There was also a significant correlation between high anti-dsDNA titre and disease activity in the active disease group compared to inactive disease and healthy controls in their study (P<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…Farkhati et al 22 stated that in SLE patients with positive anti-dsDNA levels, severe disease activity was present and they had higher mortality rate. Another study from Dhason et al 23 revealed that anti-dsDNA antibody level was positive in 83% of all patients with active lupus and 66% of them had high titre of anti-dsDNA levels (>10 IU/ml). There was also a significant correlation between high anti-dsDNA titre and disease activity in the active disease group compared to inactive disease and healthy controls in their study (P<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…The level of C3 and C4 in serum are used as indicators of complement consumption in SLE because activation of the complement occurs during the course of active disease, so lower levels of complement indicate a higher level of disease activity in SLE. 4 Lymphopenia is a common clinical manifestation in systemic lupus erythematosus (SLE) and is one of the diagnostic criteria. 9 Lymphopenia was observed in 62% of adult patients at the diagnosis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are various method to quantify disease activity, identify flares and to predict flares. 2,4 Serological tests are commonly used to assess the disease activity and predict lupus flare including complement (C3 and C4) test. 2,4,5 During active disease, usually there is a fall in complement levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic lupus erythematosus (SLE) is a systemic chronic inflammatory autoimmune disorder that affects multiple organs. It predominantly affects women, with a female-to-male ratio of 6-12:1 and a peak incidence during the reproductive age span [ 1 , 2 ]. One of the challenging aspects of SLE is the wide spectrum of clinical manifestations due to multisystem involvement and the progressive nature of the disease.…”
Section: Introductionmentioning
confidence: 99%